2009
DOI: 10.1261/rna.1584209
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of the tmRNA–ribosome interaction

Abstract: Trans-translation is a process which switches the synthesis of a polypeptide chain encoded by a nonstop messenger RNA to the mRNA-like domain of a transfer-messenger RNA (tmRNA). It is used in bacterial cells for rescuing the ribosomes arrested during translation of damaged mRNA and directing this mRNA and the product polypeptide for degradation. The molecular basis of this process is not well understood. Earlier, we developed an approach that allowed isolation of tmRNA-ribosomal complexes arrested at a desire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Further steps of trans-translation cause the A79-A86 loop to occupy the mRNA-binding pocket and this position is fixed by pK1. These elements remain bound to this site during the whole trans-translation process in agreement with our chemical probing data (42). The detailed models and description for modeling process are available at: http://rnp.genebee.msu.ru/bin/ view/Projects/TmrnaEnglish.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Further steps of trans-translation cause the A79-A86 loop to occupy the mRNA-binding pocket and this position is fixed by pK1. These elements remain bound to this site during the whole trans-translation process in agreement with our chemical probing data (42). The detailed models and description for modeling process are available at: http://rnp.genebee.msu.ru/bin/ view/Projects/TmrnaEnglish.…”
Section: Introductionsupporting
confidence: 82%
“…We showed that stable secondary structure elements of the tmRNA molecule remain intact at different steps of trans-translation. The tmRNA arch becomes movable and can occupy any position between the head and the shoulder of the 30S ribosomal subunit (42). We were also able to show that one SmpB molecule remains in the tmRNA complex at different stages of trans-translation elongation (43).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…The model resulting from this study suggests a positioning of PK1 and H2 nearby the E-site. 76 The dynamics of the other modules are more elusive and mainly depend on when helix H5 will come out of the ribosome and unwound to be correctly translated into the mRNA path.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%